2007
DOI: 10.1021/bm061119o
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of Oligosaccharides onto Synthetic Polymer Colloids

Abstract: A new method to form colloidally stable oligosaccharide-grafted synthetic polymer particles has been developed. The oligosaccharides, of weight-average degree of polymerization approximately 38, were obtained by enzymatic debranching of amylopectin. Through the use of a cerium(IV)-based redox initiation process, oligosaccharide chains are grafted onto a synthetic polymer colloid comprising electrostatically stabilized poly(methyl methacrylate) or polystyrene latex particles swollen with methyl methacrylate mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 53 publications
0
49
0
1
Order By: Relevance
“…In these conditions, the spontaneous anionic polymerization of ACA is sufficiently delayed to allow the occurrence of a redox radical polymerization initiated by dextran in presence of cerium (IV) ions affording latex particles mainly composed of dextran-b-PACA copolymer with surface active-properties. [62] Mange et al [60] reported a new method of latex stabilization where linear oligosaccharides (DP % 38), obtained by enzymatic debranching of starch, are grafted onto poly(methyl methacrylate) latex particles swollen with methyl methacrylate monomer. Ce(IV) was used to create initiating radicals on these oligosaccharide chains, which then propagate, initially with aqueous-phase monomer, then with the methyl methacrylate monomer inside the particles.…”
Section: Self-assembly Of Polysaccharide Block Copolymers In Selectivmentioning
confidence: 99%
See 1 more Smart Citation
“…In these conditions, the spontaneous anionic polymerization of ACA is sufficiently delayed to allow the occurrence of a redox radical polymerization initiated by dextran in presence of cerium (IV) ions affording latex particles mainly composed of dextran-b-PACA copolymer with surface active-properties. [62] Mange et al [60] reported a new method of latex stabilization where linear oligosaccharides (DP % 38), obtained by enzymatic debranching of starch, are grafted onto poly(methyl methacrylate) latex particles swollen with methyl methacrylate monomer. Ce(IV) was used to create initiating radicals on these oligosaccharide chains, which then propagate, initially with aqueous-phase monomer, then with the methyl methacrylate monomer inside the particles.…”
Section: Self-assembly Of Polysaccharide Block Copolymers In Selectivmentioning
confidence: 99%
“…[59] The mechanism involves the formation of a complex between ceric ions and hydroxyl groups followed by its disproportionation which generates an aldehyde or ketone and a free radical through the CÀC bond cleavage of 1,2-diol. [58,60] It has been shown that grafting on polysaccharide chains occurs predominantly at the reducingend hemiacetal group and at the C2ÀC3 glycol groups in anhydroglucose units. [61] Few studies reported on the use of cerium oxidation for synthesizing block copolymers from polysaccharides.…”
mentioning
confidence: 99%
“…Another interesting reaction of Ce 4+ with starch takes place at the hemiacetal reducing end of the starch molecule, where the reaction with Ce 4+ is much faster than at the 1,2‐diols in the body of the starch chains 8, 10. Contrary to our previous work using oligosaccharides,11 the starches used in this work are amylopectins with molecular weights of the order of 10 7 to 10 8 . As there is only one reducing end per starch molecule and 10 5 to 10 6 anhydroglucose units in amylopectin, it follows that most radical sites formed by direct Ce 4+ oxidation of amylopectin will be in the body of the starch chains.…”
Section: Introductionmentioning
confidence: 75%
“…There exists an additional possibility that the water phase starches are grafted to the synthetic monomer during the nucleation phase to the point where they would reach their critical chain length and be hydrophobic enough to form a particle, but this is evidently not the dominant mechanism (i.e., the viscosity of the latex would not increase drastically by the end of the polymerization). A common strategy for including polysaccharides in emulsion polymerizations while maintaining stability (i.e., in regards to viscosity) is to severely reduce their molecular weight, often in situ …”
Section: Resultsmentioning
confidence: 99%